Design of Low Cost Smart Insole for Real Time Measurement of Plantar Pressure. (2015) - Tan, Adin Ming; Fuss, Franz Konstantin; Weizman, Yehuda; Woudstra, Ydwer; Troynikov, Olga
Abstract: Real time plantar pressure provides information critical to the understanding of gait mechanics and has a wide range of applications. In this study, smart insoles were designed and developed to measure real time foot plantar pressure. Key features of the insoles included cost-effectiveness, good working pressure detection range, wireless data transfer and real-time data analysis. Calibration of the sensing material was done and the resulting accuracy of the insoles was compared to that of a Kistler force plate, achieving an r 2 value of 0.981. Real-time visualization of pressure mapping was incorporated to enable intuitive understanding of relative plantar pressure distribution.